Cardiovascular screening of adolescent athletes - Siddiqui, S.; Patel, D. R. (Pediatric Clinics of North America, 2010)
A preparticipation cardiovascular screening is recommended for all athletes with the aim of identifying conditions that increase the risk for adverse cardiac event, including sudden death. History and physical examination are the mainstay of cardiovascular screening of young athletes. The ability to identify athletes at risk, however, based on history and physical examination alone is low, and inclusion of an electrocardiogram as a screening tool has been suggested to improve the sensitivity of screening. This article provides an overview of key aspects of cardiovascular screening currently recommended in the United States for young athletes.